PASTURABLE ECOSYSTEMS RESTIRATION, SUBJECT TO ANTHROPOGENOUS PRESSURE - R. Z. Usmanov; M. A. Babaeva; S. V. Osipova (Юг России: экология, развитие)
Consecutive stages of soil formation at restoration of the degraded areas are shown. The general regularities and renewal conditions of a soil cover and pasturable vegetation during functional restoration i.e. the grounds, broken in result of technogenic and agrarian influence are revealed.